Sub-Nanosecond Clock and Data Recovery in an Optically-Switched Data Centre Network - Clark, Kari; Ballani, Hitesh; Bayvel, Polina; Cletheroe, Daniel; Gerard, Thomas; Haller, Istvan; Jozwik, Krzysztof; Shi, Kai; Thomsen, Benn; Watts, Philip; Williams, Hugh; Costa, Paolo; et al. (44th European Conference on Optical Communication (ECOC Post-deadline paper), 2018)
We demonstrate a clock and data recovery technique that achieves <625ps locking time for 25.6Gb/s-OOK and show its robustness under worst-case data centre temperature variation. The locking time was improved by 12×, making nanosecond optical switching viable in data centres.